Recovery in Embryonated Eggs of Viable but Nonculturable Campylobacter jejuni Cells and Maintenance of Ability To Adhere to HeLa Cells after Resuscitation - Cappelier, J. M. (American Society for Microbiology, 1999)
The existence of a viable but nonculturable (VBNC) state has been described for Campylobacter jejuni as it had been for a number pathogenic bacteria. Three C. jejuni human isolates were suspended in surface water and subsequently entered the VBNC state. After starvation for 30 days, VBNC cells were inoculated in the yolk sacs of embryonated eggs. Culturable cells were detected in a large proportion of the embryonated eggs inoculated with VBNC C. jejuni cells. Recovered cells kept their adhesion properties.